Some Results on Conditionally Compatible and Conditionally Semi-Compatible Mappings in Probabilistic 2-Metric Space - Satyanna, K.; Srinivas, V. (Communications in Mathematics and Applications, 2022)
The objective of this paper is to obtain two results in probabilistic 2-metric space by employing the concepts of (E.A)-property, conditionally compatible, conditionally semi-compatible and sub-sequentially continuous mappings. These findings improve the theorem proved in [5]. Further, these results are substantiated by supporting examples.